Advanced Laser Diode Reliability - Vanzi, Massimo, editor 651523; Béchou, Laurent, editor 651524; Fukuda, Mitsuo, editor 651525; Mura, Giovanna, editor 651526; ScienceDirect (Online service) 7722 (San Diego : ISTE Press-Elsevier, 2021)
Advanced Laser Diode Reliability focuses on causes and effects of degradations of state-of-the-art semiconductor laser diodes. It aims to provide a tool for linking practical measurements to physical diagnostics. To this purpose, it reviews the current technologies, addressing their peculiar details that can promote specific failure mechanisms. Two sections will support this kernel: a) Failure Analysis techniques, procedures and examples; b) Device-oriented laser modelling and parameter extraction.